2004
DOI: 10.4049/jimmunol.173.6.3599
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Serotonin Is a Chemotactic Factor for Eosinophils and Functions Additively with Eotaxin

Abstract: Elevated levels of serotonin (5-hydroxytryptamine, 5-HT) are observed in the serum of asthmatics. Herein, we demonstrate that 5-HT functions independently as an eosinophil chemoattractant that acts additively with eotaxin. 5-HT2A receptor antagonists (including MDL-100907 and cyproheptadine (CYP)) were found to inhibit 5-HT-induced, but not eotaxin-induced migration. Intravital microscopy studies revealed that eosinophils roll in response to 5-HT in venules under conditions of physiological shear stress, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 18 publications
4
82
0
1
Order By: Relevance
“…Serotonin directly modulates functions of several other immune cells, but unlike in the case of dendritic cells, mast cells, and eosinophils, serotonin did not act as a chemoattractant to induce in vitro migration of neutrophils. 7,[41][42][43][44] In vitro plateletneutrophil rosetting was also independent of the platelet serotonin content, indicating that serotonin does not influence platelet P-selectin expression and platelet-neutrophil interactions. It is more probable that serotonin enhances neutrophil extravasation by regulating endothelial selectin expression, because serotonin induces WPB exocytosis in cultured endothelial cells 10,11 and injection of serotonin enhanced leukocyte rolling in the Tph1 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 96%
“…Serotonin directly modulates functions of several other immune cells, but unlike in the case of dendritic cells, mast cells, and eosinophils, serotonin did not act as a chemoattractant to induce in vitro migration of neutrophils. 7,[41][42][43][44] In vitro plateletneutrophil rosetting was also independent of the platelet serotonin content, indicating that serotonin does not influence platelet P-selectin expression and platelet-neutrophil interactions. It is more probable that serotonin enhances neutrophil extravasation by regulating endothelial selectin expression, because serotonin induces WPB exocytosis in cultured endothelial cells 10,11 and injection of serotonin enhanced leukocyte rolling in the Tph1 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 96%
“…Time-lapse imaging of interneurons in embryonic slices revealed that the application of 5-HT decreased Evidence for a role of 5-HT in cell migration has been demonstrated in nonneuronal cells such as eosinophils in the immune system, 31 pulmonary artery cells, 32 aortic endothelial cells 33 and mesenchymal cells derived from the cranial neural crest. 34 Interestingly in the nematode Caenorhabditis elegans, long-distance neuronal migration was shown to be under the regulation of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…In most phyla, 5-HT triggers motility of various cell types including vertebrate lymphocytes (chick, fish, rodent [185,186]) and microglia towards the CNS [170]. In the mammalian cortex, a role for 5-HT in regulating the migration of cortical neurons has recently emerged.…”
Section: Serotonin and Neuronal Migrationmentioning
confidence: 99%